2020
DOI: 10.34172/jlms.2020.52
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of Low-Level Laser Therapy in the Treatment of Bell’s Palsy in Diabetic Patients

Abstract: Introduction: The most common causes of the abrupt onset of unilateral facial weakness are stroke and Bell’s palsy. The drug regimen together with electrical stimulation was more effective in treating Bell’s palsy than conventional drug treatment alone. We aimed to evaluate more effective and safe therapies for the treatment of Bell’s palsy. Methods: This clinical interventional study was conducted on 30 diabetic patients with Bell’s palsy who referred to a pain clinic for 1 year and were treated by low-leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 26 publications
0
18
0
Order By: Relevance
“…All researchers in the descriptive studies reported improvement of Bell's palsy on House-Brackman (H-B) grade following LLLT at the ending of their treatment sessions. The effect of LLLT on the treatment of Bell's palsy has also been reported in diabetic patients, 23 children, 26,29 and chronic Bell's palsy. 28 When reviewed the human studies, there were no reported adverse effects during treatment and/or follow-up sessions.…”
Section: Resultsmentioning
confidence: 91%
See 2 more Smart Citations
“…All researchers in the descriptive studies reported improvement of Bell's palsy on House-Brackman (H-B) grade following LLLT at the ending of their treatment sessions. The effect of LLLT on the treatment of Bell's palsy has also been reported in diabetic patients, 23 children, 26,29 and chronic Bell's palsy. 28 When reviewed the human studies, there were no reported adverse effects during treatment and/or follow-up sessions.…”
Section: Resultsmentioning
confidence: 91%
“…[17][18][19] Of 8 human studies, 2 studies were designed as randomized controlled study (RCT) 21,22 and 6 studies were descriptive studies (Table 2). [23][24][25][26][27][28] One study had two parallel RCT design, the LLLT group and control group. 21 The other study had three parallel RCT design including highlevel laser therapy, LLLT group, and control group.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, their recovery was prevalently a partial result [40]. Aghamohamdi et al [41] showed that the House-Brackmann grading scale ameliorates to grade I (18 cases), grade II (six cases), and grade IV (six cases) through 12 sessions of PBM on 30 patients with diabetes. Lastly, Ordahan and Karahan [42] observed positive effects of PBM associated with expression exercises on 23 patients treated in the subacute phase of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…Aghamohamdi and co-authors, in a clinical study on 30 diabetic patients with Bell's palsy, demonstrated that PBM is a safe, reliable, and proper alternative approach for the treatment of facial nerve palsy, especially in the presence of underlying conditions such as diabetes mellitus [ 19 ].…”
Section: Introductionmentioning
confidence: 99%